Impact Assessment of Climate Change Knowledge Network in Indian Agriculture (CCKN-IA) of selected blocks of Jharkhand, Maharashtra and Odisha States - Bhaskar, G (Journal of Agricultural Extension Management, 2018)
The study on Impact Assessment of Climate Change Knowledge Network in Indian Agriculture (CCKN-IA) is an ex-post impact evaluation study that intended to establish comparative learnings such that the CCKNâ€“IA approach could be easily replicated across blocks of the entire state. The CCKN project was implemented in three states namely Jharkhand, Odisha and Maharashtra during 2015 â€“ 2017. The study focuses on the extent of access to climate adaptive advisories, from the responses of the project and control farmers. It is found that the project farmers had higher access to climate adaptive advisories than control village farmers in crop production practices. As far as the adoption of climate adaptive advisories are concerned, the farmers of project villages in all the three states reported a higher adoption of climate adaptive advisories in crop production than that of the control villages. Assuming the project benefits in the pilot blocks, the same concept of CCKN-IA project can be upscaled. Accordingly the cost of implementation has been worked out and presented in this paper, so that the respective State Governments can adopt the CCKN-IA project in the entire state.Â